"NOBODY DESERVES THIS": ADOLESCENT SEXUAL ASSAULT VICTIMS' PERCEPTIONS OF DISBELIEF AND VICTIM BLAME FROM POLICE. Issue 1 (January 2016) - Greeson, Megan R.; Campbell, Rebecca; Fehler‐Cabral, Giannina
Abstract : Prior research reveals that many police engage in victim blaming, skeptical reactions to adult sexual assault survivors. However, little is known about adolescent survivors' experiences with police. To address this gap, qualitative interviews were conducted with 20 adolescent rape survivors to understand adolescents' perceptions of their interactions with the police (specifically the messages the officers conveyed about the assault and the victims themselves). Positive perceptions occurred when the adolescents perceived police behavior as indications of believing their story, validating their decision to report, and refraining from judgment of their behavior. On the other hand, negative perceptions were associated with behaviors that were viewed as indications of skepticism, blame, or judgment. Specific behaviors that were associated with each of these themes are discussed. Interactions with the police influenced survivors' emotional well‐being and their hope for their case's success. Implications for improving interactions between police and adolescent sexual assault victims are discussed.